Optimization of Ladle Tilting Speed for Preventing Temperature Drops in the Die Casting Process - Ando, Haru; Minamide, Daichi; Takagi, Yuto; Yano, Ken’ichi; Nakamura, Naoto; Sano, Masahiro; Aoki, Takahiro; Nemoto, Yasunori (Journal of Casting & Materials Engineering, 2022)
In die casting, molten metal poured into a shot sleeve is pressed into a mold by a plunger at high speed. The temperature of the metal drops significantly while it is being poured from the ladle to the shot sleeve, resulting in casting defects such as misrun flow lines. Although it is important to control the temperature at all stages of the process, a method for minimizing temperature loss has not yet been clarified to date. In this study, the cause of the temperature drop in the shot sleeve was clarified, and a method of optimizing the ladle tilting speed was proposed to prevent temperature drop. First, experiments were conducted to measure the decrease in metal temperature in the sleeve during pouring. These experiments revealed that the metal cools significantly from the moment it touches the shot sleeve. Therefore, the time from the first contact between the shot sleeve and the metal to the start of pouring was set as the objective function. A genetic algorithm was then used to derive the optimal ladle tilting speed pattern to suppress the temperature drop. This analysis confirmed that the metal was poured without flowing out or running ahead and that the immediate liquid level vibration after pouring was suppressed, thus ensuring stable pouring.